Ocean acidification through the lens of ecological theory. Issue 1 (1st January 2015) - Gaylord, Brian; Kroeker, Kristy J.; Sunday, Jennifer M.; Anderson, Kathryn M.; Barry, James P.; Brown, Norah E.; Connell, Sean D; Dupont, Sam; Fabricius, Katharina E.; Hall-Spencer, Jason M.; Klinger, Terrie; Milazzo, Marco; et al.
Abstract : Ocean acidification, chemical changes to the carbonate system of seawater, is emerging as a key environmental challenge accompanying global warming and other human‐induced perturbations. Considerable research seeks to define the scope and character of potential outcomes from this phenomenon, but a crucial impediment persists. Ecological theory, despite its power and utility, has been only peripherally applied to the problem. Here we sketch in broad strokes several areas where fundamental principles of ecology have the capacity to generate insight into ocean acidification's consequences. We focus on conceptual models that, when considered in the context of acidification, yield explicit predictions regarding a spectrum of population‐ and community‐level effects, from narrowing of species ranges and shifts in patterns of demographic connectivity, to modified consumer–resource relationships, to ascendance of weedy taxa and loss of species diversity. Although our coverage represents only a small fraction of the breadth of possible insights achievable from the application of theory, our hope is that this initial foray will spur expanded efforts to blend experiments with theoretical approaches. The result promises to be a deeper and more nuanced understanding of ocean acidification and the ecological changes it portends.